2013
DOI: 10.1002/bip.22152
|View full text |Cite
|
Sign up to set email alerts
|

Electron transfer dynamics of peptide‐derivatized RuII‐polypyridyl complexes on nanocrystalline metal oxide films

Abstract: The performance of dye-sensitized solar and photoelectrochemical cells is strongly dependent on the electron transfer events at the electrode-sensitizer interface. Surface-bound peptides derivatized with chromophores have not been used in dye-sensitized solar and photoelectrochemical cells, but they have properties for these applications that could be advantageous by exploiting secondary structure and the attachment of multiple chromophores. In this manuscript, we have investigated structure-property relations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 62 publications
0
11
0
Order By: Relevance
“…Assuming that k r and k nr for TiO 2 −RuC and TiO 2 −(X)−Zr−RuC are similar to ZrO 2 − RuC, k inj can be calculated by using τ = 1/(k r + k nr + k inj ). 4 The calculated electron injection rate constant increases in the order a Measured using an integrating sphere. b Weighted average lifetime from the biexponential fit (ex: 445 nm).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Assuming that k r and k nr for TiO 2 −RuC and TiO 2 −(X)−Zr−RuC are similar to ZrO 2 − RuC, k inj can be calculated by using τ = 1/(k r + k nr + k inj ). 4 The calculated electron injection rate constant increases in the order a Measured using an integrating sphere. b Weighted average lifetime from the biexponential fit (ex: 445 nm).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Electron transfer from a photoexcited chromophore to a semiconducting metal oxide surface is a critical event in dye-sensitized solar cells and dye-sensitized photoelectrosynthesis cells. Considerable efforts have been dedicated to manipulate electron transfer rates at these interfaces by reducing the electronic coupling between the dye and semiconductor which in turn slows the electron transfer rates. Spatial separation of the dye and semiconductor is arguably the most common method of reducing electronic coupling and is achieved by two primary strategies: (1) atomic layer deposition (ALD) and (2) synthetic modification of the dye.…”
Section: Introductionmentioning
confidence: 99%
“…Photoinduced oxidation of RuBPY derivatives doped onto SnO 2 and TiO 2 dispersions and films has been well established and could explain the quenched lifetime of RuDCBPY in UiO-67/FTO. Therefore, to ascertain the role of the FTO substrate as a potential quencher of the RuDCBPY 3 MLCT, films were also grown on conventional SiO 2 -based glass slides since SiO 2 is known to be insulating and, consequently, does not participate in electron transfer with adsorbed RuBPY. It should be noted that RuDCBPY-UiO67/glass films loaded below 10 m m were difficult to obtain (even under synthetic conditions in which RuDCBPY mole ratios were <1% relative to BPDC). However, at RuDCBPY doping concentrations of 14 m m and above, the observed emission maxima of films on glass were found to be independent of doping concentration ranging between 630 and 640 nm (Figure S4 in Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…Since there is a parallel between our recent work in understanding the role of semiconducting oxide nanoparticles in enhancing the Raman activities of molecules adsorbed on them and the characteristics of peptide–metal oxide nanointerfaces, we thought it would be interesting to investigate them. In our work on surface enhanced Raman scattering (SERS) on semiconducting nanoparticles, we have shown that the enhancement of Raman activities arises from a large increase in polarizability due to charge transfer from the molecule to the semiconducting nanoparticle. , Furthermore, we have delineated the specific role of factors like metal oxide composition, nanoparticle size, solvent, and pH on the observed Raman activities .…”
mentioning
confidence: 99%
“…Given the recent interest in biophotovoltaic devices and the necessity of understanding the role played by small polypeptide chains adsorbed on semiconducting nanoparticles in directing and controlling rates of electron transfer, , we directed our attention to investigating the nature of charge transfer at peptide–metal oxide nanointerfaces. Our focus is to examine the role of both peptide secondary structure and the presence of cationic amino acids in the peptide in influencing both the binding energetics and the interfacial electronic characteristics. In order to address these twin issues, we carried out calculations on the A6K and A7 (Ac-AAAA­AAA-NH 2 ) peptides.…”
mentioning
confidence: 99%